An RNA polymerase II transcription factor inactivated in poliovirus-infected cells copurifies with transcription factor TFIID. - Kliewer, S (1988)
Inhibition of host cell RNA polymerase II-mediated transcription by poliovirus infection was studied in vitro. Whole-cell extracts prepared from poliovirus-infected HeLa cells at 3 h postinfection were shown to be deficient in a factor required for specific transcription from the adenovirus major late promoter. Three lines of evidence suggest that transcription factor TFIID is deficient in poliovirus-infected cells. First, the activity required to specifically restore transcription in poliovirus-infected cell extracts was shown to copurify with TFIID through three chromatographic steps. Second, transcription reactions reconstituted with phosphocellulose-derived chromatographic fractions revealed a fourfold decrease in the specific activity of the TFIID-containing fraction prepared from poliovirus-infected cells compared with that of the same fraction prepared from mock-infected cells. Finally, TFIID and the activity required to specifically restore transcription in virus-infected cell extracts were shown to have the same kinetics of heat inactivation. Together, these results suggest that inactivation of TFIID is an early event in the inhibition of host cell RNA polymerase II transcription by poliovirus.